2018
DOI: 10.7717/peerj.4453
|View full text |Cite
|
Sign up to set email alerts
|

Changes in nutrients and decay rate of Ginkgo biloba leaf litter exposed to elevated O3 concentration in urban area

Abstract: Ground-level ozone (O3) pollution has been widely concerned in the world, particularly in the cities of Asia, including China. Elevated O3 concentrations have potentially influenced growth and nutrient cycling of trees in urban forest. The decomposition characteristics of urban tree litters under O3 exposure are still poorly known. Ginkgo biloba is commonly planted in the cities of northern China and is one of the main tree species in the urban forest of Shenyang, where concentrations of ground-level O3 are ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 46 publications
1
1
0
Order By: Relevance
“…Similar to our findings, more mass remained in leaf litter of yellow poplar (Liriodendron tulipifera L.) exposed to ambient or elevated O 3 (relative to charcoal-filtered air) in the first 10 months of incubation, but these differences no longer existed by the end of the year (Boerner and Rebbeck 1995). Likewise, elevated O 3 decelerated the leaf litter (Ginkgo biloba L.) decomposition early in the incubation period and slightly accelerated it in later stages of the incubation (Fu et al 2018). While the difference in decay rate may be temporal, it may have implications to various ecological processes, including nutrient cycling processes.…”
Section: O 3 and Edu Effects On Leaf Litter Decaysupporting
confidence: 88%
See 1 more Smart Citation
“…Similar to our findings, more mass remained in leaf litter of yellow poplar (Liriodendron tulipifera L.) exposed to ambient or elevated O 3 (relative to charcoal-filtered air) in the first 10 months of incubation, but these differences no longer existed by the end of the year (Boerner and Rebbeck 1995). Likewise, elevated O 3 decelerated the leaf litter (Ginkgo biloba L.) decomposition early in the incubation period and slightly accelerated it in later stages of the incubation (Fu et al 2018). While the difference in decay rate may be temporal, it may have implications to various ecological processes, including nutrient cycling processes.…”
Section: O 3 and Edu Effects On Leaf Litter Decaysupporting
confidence: 88%
“…A few studies showed before that O 3 can alter the decomposition process using various plant species (Boerner and Rebbeck 1995;Baldantoni et al 2013), albeit there is a discrepancy in the findings (Parsons et al 2004(Parsons et al , 2008Lindroth 2010;Vitale et al 2019). Ozone slowed down (Parsons et al 2008;Baldantoni et al 2013;Fu et al 2018), enhanced (Fenn and Dunn 1989;Boerner and Rebbeck 1995;Parsons et al 2008;Fu et al 2018), or did not significantly affect (Boerner and Rebbeck 1995;Fu et al 2018) biomass loss of leaf litter. These differences can be attributed to various factors such as species, incubation duration, and O 3 exposure characteristics.…”
Section: O 3 and Edu Effects On Leaf Litter Decaymentioning
confidence: 99%